(untitled) (Informatica, 2024)
With advances in information and communication technologies and rapid computing and technological progress, modeling, and simulation of real problems, has become the most important teaching and learning method in educational process. Representing and explaining processes through simulations can enable students to easier understand these processes and discover the essential properties of a system. In many situations, in learning different subjects it is not possible to experiment with real objects to find the right solutions, therefore modelling and simulation can be used to build models that represent the real systems. Agent-based modelling (ABM) is a powerful simulation modelling technique, that can be easily incorporated in learning and teaching processes. Agent based modelling (ABM) is a relatively new method compared to system dynamics and discrete event modelling. In ABM a system is modelled as a collection of autonomous decision-making entities called agents, that can interact among each other’s. In this paper, the agent-based modelling simulation is considered as a tool in educational process for learning and teaching different subjects. Anylogic software is used for some simulation examples of agent-based modelling that can be used in educational process.